Institutional Strengthening in Waste Management in Medan, Binjai, Deli Serdang, Karo (Mebidangro) - Hatta Ridho; M. Arif Nasution; Subhilhar Subhilhar; Muryanto Amin (Budapest International Research and Critics University, 2021)
Weak coordination can also be seen in the achievement of cooperation agreements between regions in the Mebidangro area. For example, how the weak coordination between Pemko Medan and Pemko Deli Serdang resulted in the closure of the TPA Namo Bintang in Pancur Batu sub-district, even though Presidential Decree No. 62/2011 has designated TPA Namo Bintang together with TPAatuh in Medan Marelan as a garbage landfill for residents of Medan city. Weak coordination certainly requires institutional strengthening that can ensure synergy among government ranks in the Mebidangro area to be able to overcome problems faced together. This research was conducted in the Mebidangro area by using qualitative which focused on the problems that existed at the time of the research or the actual problems as well as the facts about the problems being investigated as they were, accompanied by sufficient rational interpretation. Data collection techniques through observation, interviews and limited group discussions. The character of the Mebidangro implementing organs has not shown an orderly working mechanism, where the two main components of the character of the implementing organs, namely the SOP and the division of tasks / authorities between the provincial government and district / city governments as well as between district / city governments throughout the Mebidangro region do not exist. Institutional strengthening is needed to strengthen the Integrated Management Institution model.